Suppression of synapsin II inhibits the formation and maintenance of synapses in hippocampal culture. - Ferreira, A (1995)
Numerous synaptic proteins, including several integral membrane proteins, have been assigned roles in synaptic vesicle fusion with or retrieval from the presynaptic plasma membrane. In contrast, the synapsins, neuron-specific phosphoproteins associated with the cytoplasmic surface of synaptic vesicles, appear to play a much broader role, being involved in the regulation of neurotransmitter release and in the organization of the nerve terminal. Here we have administered antisense synapsin II oligonucleotides to dissociated hippocampal neurons, either before the onset of synaptogenesis or 1 week after the onset of synaptogenesis. In both cases, synapsin II was no longer detectable within 24-48 h of treatment. After 5 days of treatment, cultures were analyzed for the presence of synapses by synapsin I and synaptophysin antibody labeling and by electron microscopy. Cultures in which synapsin II was suppressed after axon elongation, but before synapse formation, did not develop synapses. Cultures in which synapsin II was suppressed after the development of synapses lost most of their synapses. Remarkably, with the removal of the antisense oligonucleotides, neurons and their synaptic connections recovered. These studies lead us to conclude that synapsin II is involved in the formation and maintenance of synapses in hippocampal neurons.